Validity, reliability and Norwegian adaptation of the Stroke-Specific Quality of Life (SS-QOL) scale. (6th January 2018) - Pedersen, Synne Garder; Heiberg, Guri Anita; Nielsen, Jørgen Feldbæk; Friborg, Oddgeir; Stabel, Henriette Holm; Anke, Audny; Arntzen, Cathrine
Background: There is a paucity of stroke-specific instruments to assess health-related quality of life in the Norwegian language. The objective was to examine the validity and reliability of a Norwegian version of the 12-domain Stroke-Specific Quality of Life scale. Methods: A total of 125 stroke survivors were prospectively recruited. Questionnaires were administered at 3 months; 36 test–retests were performed at 12 months post stroke. The translation was conducted according to guidelines. The internal consistency was assessed with Cronbach's alpha; convergent validity, with item-to-subscale correlations; and test–retest, with Spearman's correlations. Scaling validity was explored by calculating both floor and ceiling effects. A priori hypotheses regarding the associations between the Stroke-Specific Quality of Life domain scores and scores of established measures were tested. Standard error of measurement was assessed. Results: The Norwegian version revealed no major changes in back translations. The internal consistency values of the domains were Cronbach's alpha = 0.79–0.93. Rates of missing items were small, and the item-to-subscale correlation coefficients supported convergent validity (0.48–0.87). The observed floor effects were generally small, whereas the ceiling effects had moderate or high values (16%–63%). Test–retest reliability indicated stability in most domains, with Spearman's rho = 0.67–0.94 (all p < 0.001), whereas the rho was 0.35 (p < 0.05) for the 'Vision' domain. Hypothesis testing supported the construct validity of the scale. Standard error of measurement values for each domain were generated to indicate the required magnitudes of detectable change. Conclusions: The Norwegian version of the Stroke-Specific Quality of Life scale is a reliable and valid instrument with good psychometric properties. It is suited for use in health research as well as in individual assessments of persons with stroke.